Utilization of Google Classroom in Vocational High School as E-Learning Based Learning - Syurfah Ayu Ithriah; Tri Lathif Mardi Suryanto; Rizka Hadiwiyanti (Future Science)
The utilization of information technology and the internet today has assisted the field of education, especially for maximizing learning method. One of the online learning method that are being developed and popular to use is Google Classroom. It is developed by Google to streamline the process of sharing files between teachers and students. This paper presents community service activity in the utilization of Google Classroom in SMK UNITOMO Surabaya. A training and practice are given to all teachers for approximately two hours, where they could learn four primary features in Google Classroom. This community service was expected to support teachers in utilizing and implementing Google Classroom for their teaching and learning activities.